2015
DOI: 10.1093/ecco-jcc/jjv203
|View full text |Cite
|
Sign up to set email alerts
|

Donor Species Richness Determines Faecal Microbiota Transplantation Success in Inflammatory Bowel Disease

Abstract: Faecal microbiota transplantation led to endoscopic and long-term (>2 years) remission in 2 out of 8 ulcerative colitis patients. Higher donor richness was associated with successful transplant. Therefore, faecal microbiota transplantation with donor prescreening could be a treatment option for selected refractory ulcerative colitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
265
6
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(300 citation statements)
references
References 49 publications
9
265
6
11
Order By: Relevance
“…Oscillibacter and Lachnospiracea incertae sedis, which are both genera of the Firmicutes phylum and the Clostridia class, were also reduced by sugar. Oscillibacter is negatively correlated with Crohn disease (65,66) and is implicated as a potential treatment for ulcerative colitis after fecal transfer (67). Lachnospiracea incertae sedis are involved in the fermentation of starches to produce SCFAs (68).…”
Section: Figurementioning
confidence: 99%
“…Oscillibacter and Lachnospiracea incertae sedis, which are both genera of the Firmicutes phylum and the Clostridia class, were also reduced by sugar. Oscillibacter is negatively correlated with Crohn disease (65,66) and is implicated as a potential treatment for ulcerative colitis after fecal transfer (67). Lachnospiracea incertae sedis are involved in the fermentation of starches to produce SCFAs (68).…”
Section: Figurementioning
confidence: 99%
“…The success of FMT in treating RCDI has been demonstrated in several studies, with cure rates exceeding 90% (van Nood et al ., 2013; Kelly et al ., 2016; Lee et al ., 2016). Use of FMT as a therapy for other gastrointestinal disorders such as IBD has been proposed (Vermeire et al ., 2016). To date, safety concerns and acceptability are main constraints of therapeutic uses of FMT.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on microbiome have expanded in order to elucidate its role in a great number of other diseases. Fecal microbiota transplantation is a successful therapy for patients with refractory Clostridium difficile infections [15] and it has also been suggested as a treatment option for inflammatory bowel disease, given a role for intestinal microbiota in this disease [16,17] . Vermeire and colleagues assessed the impact of fecal microbiota transplantation in patients with inflammatory bowel disease and studied predictors of clinical (non)response in microbial profiles of donors and patients and concluded that fecal microbiota transplantation led to endoscopic and long-term (> 2 years) remission in 2 out of 8 ulcerative colitis patients [16] .…”
Section: Obesity and Gut Epithelium -What Is Already Known?mentioning
confidence: 99%
“…Fecal microbiota transplantation is a successful therapy for patients with refractory Clostridium difficile infections [15] and it has also been suggested as a treatment option for inflammatory bowel disease, given a role for intestinal microbiota in this disease [16,17] . Vermeire and colleagues assessed the impact of fecal microbiota transplantation in patients with inflammatory bowel disease and studied predictors of clinical (non)response in microbial profiles of donors and patients and concluded that fecal microbiota transplantation led to endoscopic and long-term (> 2 years) remission in 2 out of 8 ulcerative colitis patients [16] . Many other experimental and clinical studies that have been published in the last years were able to confirm that the composition of the intestinal flora shows differences between lean and obese subjects [18][19][20][21][22] .…”
Section: Obesity and Gut Epithelium -What Is Already Known?mentioning
confidence: 99%